From Oral to Sublingual: A Redefined Avanafil Tablet with a Breakthrough in Bioavailability and First-Pass Metabolism Avoidance - Asar TO; Al-hejaili OD; El-Sawy HS; Abd-Allah FI; Omar AM; Ahmed TA; El-Say KM (Drug Design, Development and Therapy)
Turky Omar Asar,1 Omar D Al-hejaili,2 Hossam S El-Sawy,3,4 Fathy I Abd-Allah,5 Abdelsattar M Omar,6 Tarek A Ahmed,2 Khalid M El-Say2 1Department of Biology, College of Science and Arts at Alkamil, University of Jeddah, Jeddah, Saudi Arabia; 2Department of Pharmaceutics, Faculty of Pharm Saudi Arabia Acy, King Abdulaziz University, Jeddah, 21589, Saudi Arabia; 3Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Egyptian Russian University, Cairo, 11829, Egypt; 4College of Pharmacy, Kut University, Wasit, 52001, Iraq; 5Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Al-Azhar University, Cairo, 11651, Egypt; 6Department of Pharmaceutical Chemistry, Faculty of Pharmacy, King Abdulaziz University, Jeddah, 21589, Saudi ArabiaCorrespondence: Khalid M El-Say, Department of Pharmaceutics, Faculty of Pharmacy, King Abdulaziz University, Jeddah, Saudi Arabia, Tel +966582934511 ; +96626400000 Ext. 20073, Fax +‏ 96626951696, Email kelsay1@kau.edu.saIntroduction: Avanafil (AVA) is a very efficient phosphodiesterase type 5 inhibitor for the treatment of erectile dysfunction. However, it has limited bioavailability when taken orally and considerable first-pass metabolism. Enhancing its solubility and choosing an alternative delivery route may enhance its effectiveness and duration of action.Methods: Eight complex formulations were elaborated and analyzed at various ratios using different polyethylene glycols and hydroxypropyl-beta-cyclodextrin (HP-β-CD). Sublingual tablets containing AVA were designed and optimized using the Quality-by-design approach. The tablets’ pre-compression and post-compression properties were evaluated. The in-vivo pharmacokinetic behavior of the optimized tablet was assessed and compared with that of the commercial oral tablets in human volunteers.Results: The HP-β-CD–AVA inclusion complex (1:1 molar ratio) showed an optimum solubilization capacity with an amount suitable for incorporation into sublingual tablets. The total amounts of superdisintegrants and Plasdone XL and the percentage of starch significantly influenced the length of time it took for 80% of the AVA to be released from the sublingual tablets, the tablet hardness, and the length of time for tablet disintegration. The optimized AVA sublingual tablet exhibited a 5.98-fold increase in the AVA mean residence time over the commercial tablet, with greater plasma exposure over 72 hours and 1356.42% relative bioavailability.Conclusion: The sublingual tablets of the solubility-enhanced HP-β-CD–AVA inclusion complex represent a promising strategy to improve AVA bioavailability and bypass the first-pass effect. Furthermore, their extended activity offers potential clinical benefits, particularly for ED patients, such as ease of administration and reduced side effects. Keywords: erectile dysfunction, avanafil, inclusion complex, sublingual tablets, pharmacokinetic study